Laminated transformer preparation method and laminated transformer
By preparing ferrite and microcrystalline glass-ceramic tapes through tape casting and combining them with isostatic pressing and controlled cooling rate methods for multilayer transformer fabrication, the problem of interfacial stress concentration during the sintering process of multilayer transformers was solved. This enabled the design of miniaturized and high-frequency multilayer transformers, improving product yield and high-frequency performance.
Patent Information
- Application Number
- CN202511553726.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-28
- Publication Date
- 2026-02-06
AI Technical Summary
During the sintering process, planar laminated transformers are prone to cracking due to the difference in the thermal expansion coefficients of the materials, which leads to stress concentration at the interface and makes it difficult to achieve the dual requirements of miniaturization and high frequency.
Ferrite and microcrystalline glass-ceramic ribbons were prepared by tape casting process, and then co-sintered after forming an intermediate electrode layer and a cap layer by stacking them in a specific sequence. By combining isostatic pressing and controlling the cooling rate, the stress concentration at the interface caused by the difference in thermal expansion coefficients was solved.
It significantly improves the product yield and reliability of multilayer transformers, realizes the integrated miniaturized design of primary coil, secondary coil and magnetic core, enhances high-frequency performance and energy conversion efficiency, and reduces heat loss.
Smart Images

Figure CN121483849A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of transformer manufacturing technology, and more specifically, to a method for preparing a multilayer transformer and a multilayer transformer. Background Technology
[0002] As terminal devices develop towards miniaturization, high integration, and high frequency, multilayer transformers, as key magnetic components, also face the dual challenges of size reduction and performance improvement. When planar multilayer transformers are co-fired with materials of different permeabilities, the difference in the thermal expansion coefficients of each layer can easily lead to interfacial stress concentration during sintering, resulting in structural cracking. Summary of the Invention
[0003] The purpose of this application is to provide a method for manufacturing a multilayer transformer and a multilayer transformer, aiming to solve the technical problem in the related art of interfacial stress concentration during sintering, which leads to structural cracking.
[0004] To achieve the above objectives, the technical solution adopted in this application is as follows: This application provides a method for manufacturing a multilayer transformer, including: The first green ceramic belt was made from ferrite powder using a casting process. The second green ceramic tape is made from microcrystalline glass-ceramic powder using a casting process; Through holes are formed on the first green ceramic tape and the second green ceramic tape, and conductive paste is filled into the through holes to obtain the first hole-filled green ceramic tape and the second hole-filled green ceramic tape, respectively. A primary coil layer and a secondary coil layer are printed on the first hole-filling green ceramic tape to form a coil hole-filling green ceramic tape; Multiple coil-filling green ceramic tapes and multiple second-filling green ceramic tapes are stacked in a predetermined order to form an intermediate electrode layer; Multiple sheets of the first green ceramic tape are stacked together to form a cover layer; The two capping layers and the intermediate electrode layer are stacked together to form a bar block, wherein the intermediate electrode layer is located between the two capping layers; The block is cut to form multiple stacked monomers; The laminated monomers are sintered to obtain a laminated transformer.
[0005] In some implementations, the process of forming a second green ceramic tape from microcrystalline glass-ceramic powder using a casting process includes: Microcrystalline glass-ceramic powder is mixed with dispersant, solvent and grinding media, and then initially dispersed to obtain a first processed body; The nanoparticles were added to a pre-dissolved binder and dispersed using a homogenizer to obtain a second treated body. The first processing body and the second processing body are mixed by high-energy ball milling to obtain a uniformly dispersed microcrystalline glass ceramic slurry; The microcrystalline glass-ceramic slurry is cast to form the second green ceramic tape.
[0006] In some implementations, the nanoparticles include one or more of the following: alumina, zirconium oxide, silicon carbide, titanium carbide, and aluminum nitride.
[0007] In some implementations, the mass of the nanoparticles is 0.1% to 10% of the mass of the microcrystalline glass-ceramic powder.
[0008] In some implementations, the magnetic permeability of the ferrite powder is greater than 400.
[0009] In some implementations, the microcrystalline glass-ceramic powder includes one or more of the following systems: MgO-Al2O3-SiO2, SiO2-Al2O3-ZnO-MgO, BaO-ZnO-MgO-SiO2, and BaO-Al2O3-SiO2.
[0010] In some implementations, stacking the two capping layers and the intermediate electrode layer together to form a bar block includes: The two cap layers and the intermediate electrode layer are stacked in a predetermined order to form a laminate; The stacked layers are subjected to isostatic pressing to form a block, wherein the isostatic pressing temperature is 50℃-90℃, the pressure is 20MPa-100MPa, and the processing time is 10 minutes-30 minutes.
[0011] In some implementations, during the cooling stage after sintering the laminated monomers, the cooling rate is from 0.1°C / min to 2°C / min.
[0012] In some implementations, the conductive paste is silver paste; The step of forming through holes on the first and second green ceramic tapes and filling the through holes with conductive paste includes: A laser is used to drill holes in the first and second green ceramic tapes to form through holes with a diameter of 50 μm to 300 μm; The through holes are filled with silver paste with a solid content greater than or equal to 85%; The silver paste in the through-hole is dried at a set temperature, which is between 50°C and 120°C.
[0013] This application provides a multilayer transformer, which is manufactured using the multilayer transformer manufacturing method described in any of the above implementations.
[0014] The method for manufacturing multilayer transformers and the beneficial effects of multilayer transformers provided in this application are mainly as follows: This application employs a tape casting process to separately prepare ferrite (first green ceramic tape) and microcrystalline glass-ceramic (second green ceramic tape), and then co-sintersects them after stacking them in a predetermined order to form an intermediate electrode layer and a cap layer. This effectively solves the problem of interfacial stress concentration and structural cracking caused by the difference in thermal expansion coefficients of different materials, significantly improving product yield and reliability. Simultaneously, this application achieves a miniaturized and highly integrated design that integrates the primary coil, secondary coil, and magnetic core into a single unit, meeting the size reduction requirements of end devices. Attached Figure Description
[0015] To more clearly illustrate the technical solutions in the embodiments of this application, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0016] Figure 1 This is a flowchart of the multilayer transformer manufacturing method provided in the embodiments of this application; Figure 2 This is an exploded view of the intermediate electrode layer provided in the embodiments of this application.
[0017] Explanation of key figure labels: 101. First through-hole green ceramic tape; 102. Second through-hole green ceramic tape; 103. Conductive via; 104. Primary coil layer; 105. Secondary coil layer. Detailed Implementation
[0018] In related technologies, planar multilayer transformers suffer from complex magnetic circuit design, high leakage inductance, and severe high-frequency losses, making it difficult to simultaneously achieve high power density and low loss characteristics. To address this, attempts have been made to optimize magnetic flux distribution by combining high- and low-permeability materials to improve magnetic circuit control performance. However, such material gradient designs still face several technical bottlenecks: First, magnetic flux control relies on material gradients; low-permeability slurries can only locally restrict magnetic flux, making precise control of inter-coil reluctance difficult. Second, during the co-firing process of multilayer heterogeneous materials, the difference in thermal expansion coefficients easily leads to stress concentration at the interface, causing cracking. Third, the dielectric loss of the dielectric material in the multilayer structure increases significantly with increasing frequency, limiting further improvements in high-frequency performance.
[0019] Therefore, this application provides a method for manufacturing a multilayer transformer and a multilayer transformer to solve the problems in related technologies; thereby achieving precise control of magnetic flux distribution, reducing interlayer stress and improving high-frequency loss while achieving material co-firing compatibility.
[0020] To make the technical problems, technical solutions, and beneficial effects to be solved by this application clearer, the following detailed description is provided in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and are not intended to limit the scope of this application.
[0021] Combination Figure 1 and Figure 2 As shown in the embodiments of this application, the method for manufacturing a multilayer transformer may include at least some or all of the following steps.
[0022] Step S10: The ferrite powder is formed into a first green ceramic tape using a casting process. The resulting ferrite (first green ceramic tape) has high magnetic permeability, which can meet the requirements of high-frequency magnetic coupling. For example, the length of the first green ceramic tape can be 150mm to 250mm, such as 150mm, 180mm, 200mm, 210mm or 250mm, and the width can be 100mm to 200mm, such as 100mm, 150mm, 180mm or 200mm.
[0023] Step S20: The microcrystalline glass ceramic powder is made into a second green ceramic tape using a casting process. The resulting microcrystalline glass ceramic (second green ceramic tape) has low dielectric loss and high insulation, which helps to reduce energy loss at high frequencies.
[0024] Step S30: Form through holes on the first green ceramic tape and the second green ceramic tape, and fill the through holes with conductive paste to obtain the first hole-filling green ceramic tape 101 and the second hole-filling green ceramic tape 102 respectively; it should be noted that the first green ceramic tape corresponds to the first hole-filling green ceramic tape 101, and the second green ceramic tape corresponds to the second hole-filling green ceramic tape 102.
[0025] Step S40: Print a primary coil layer 104 and a secondary coil layer 105 on the first through-hole green ceramic tape 101 to form a through-hole green ceramic tape. Exemplarily, the primary coil layer 104 and the secondary coil layer 105 can be circular. The primary coil layer 104 and the secondary coil layer 105 can be concentrically arranged. The number of primary coil layers 104 and the number of secondary coil layers 105 can be one or more. The secondary coil layer 105 is located inside the primary coil layer 104, that is, the diameter of the primary coil layer is larger than the diameter of the secondary coil layer 105.
[0026] Step S50: Multiple coil-filled green ceramic tapes and multiple second-filled green ceramic tapes 102 are stacked in a preset order to form an intermediate electrode layer. Exemplarily, stacking involves pressing multiple green ceramic tapes together to form a single unit. Alternatively, the intermediate electrode layer can be formed by alternating layers of multiple coil-filled green ceramic tapes and multiple second-filled green ceramic tapes 102, with a second-filled green ceramic tape 102 between adjacent coil-filled green ceramic tapes. It is understood that in some other possible embodiments, the intermediate electrode layer may also be formed by stacking multiple coil-filled green ceramic tapes, then stacking at least one second-filled green ceramic tape 102, then stacking one or more coil-filled green ceramic tapes, and then continuing to stack at least one second-filled green ceramic tape 102 until the stacking is completed in a preset order.
[0027] Step S60: Stack multiple first green ceramic strips to form a capping layer; the capping layer contains only ferrite material and has a relatively uniform structure. This makes stress concentration mainly occur at the interface between the capping layer and the intermediate electrode layer during the sintering of the entire block subsequently generated, thereby simplifying stress management and helping to prevent structural cracking.
[0028] Step S70: Stack the two cover layers and the intermediate electrode layer together to form a block, wherein the intermediate electrode layer is located between the two cover layers. By sandwiching the intermediate electrode layer, which contains the coil and the insulating layer of microcrystalline glass-ceramic material, between the two ferrite cover layers, a complete sandwich-style laminated structure of the transformer is formed. This achieves a high degree of vertical integration of the coil, the magnetic core, and the insulating medium. Exemplarily, the two cover layers serve as the upper and lower cover of the laminated transformer, respectively.
[0029] Step S80: Cut the block to form multiple stacked monomers.
[0030] Step S90: Sinter the laminated monomers to obtain a laminated transformer.
[0031] The multilayer transformer fabrication method provided in this application employs a tape casting process to prepare ferrite (first green ceramic tape) and microcrystalline glass-ceramic (second green ceramic tape) separately. After stacking them in a predetermined order to form an intermediate electrode layer and a cap layer, co-sintering is performed. This effectively solves the problem of interface stress concentration and structural cracking caused by differences in the thermal expansion coefficients of different materials, significantly improving product yield and reliability. Simultaneously, it achieves a miniaturized and highly integrated design that integrates the primary coil, secondary coil, and magnetic core into a single unit, meeting the size reduction requirements of end-devices. Furthermore, the use of microcrystalline glass-ceramic as a non-magnetic isolation layer introduces a controlled air gap effect, which not only enhances the transformer's DC bias withstand capability and prevents magnetic saturation but also optimizes the performance and efficiency of magnetic components at high frequencies, thus achieving the dual goals of size reduction and performance improvement.
[0032] In some embodiments, the permeability μ of the ferrite powder is greater than 400. This ensures that the magnetic field generated by the coil can be efficiently concentrated inside the core, thereby improving the magnetic coupling efficiency between the primary and secondary coils, reducing magnetic flux leakage (leakage inductance), and ultimately improving the energy transmission efficiency of the transformer.
[0033] In some embodiments, the microcrystalline glass-ceramic powder includes one or more of the following systems: MgO-Al2O3-SiO2, SiO2-Al2O3-ZnO-MgO, BaO-ZnO-MgO-SiO2, and BaO-Al2O3-SiO2. For example, the chemical composition of the MgO-Al2O3-SiO2 system includes MgO, Al2O3, and SiO2; the chemical composition of the SiO2-Al2O3-ZnO-MgO system includes SiO2, Al2O3, ZnO, and MgO; the chemical composition of the BaO-ZnO-MgO-SiO2 system includes BaO, ZnO, MgO, and SiO2; and the chemical composition of the BaO-Al2O3-SiO2 system includes BaO, Al2O3, and SiO2. By selecting a specific microcrystalline glass-ceramic system, precise control of the transformer's electrical performance (such as inductance and insulation) can be achieved while simultaneously addressing stress cracking problems.
[0034] In some embodiments, for step S20, the method of forming a second green ceramic tape from microcrystalline glass-ceramic powder using a casting process includes: Step S201: The microcrystalline glass-ceramic powder is mixed with a dispersant, a solvent, and a grinding media, and then initially dispersed to obtain a first processed body. Exemplarily, the dispersant may include one or more of organic acid salt dispersants, polymeric dispersants, or surfactant dispersants; organic acid salt dispersants include one or more of sodium citrate, sodium acetate, or sodium tartrate; polymeric dispersants include one or more of polyvinyl alcohol (PVA), polyacrylic acid (PAA), or polyvinylpyrrolidone (PVP); surfactant dispersants include one or more of sodium dodecylbenzene sulfonate (SDBS) or polyoxyethylene ether (OP-10). The solvent may be an alcohol ester solvent; the grinding media may be zirconium balls. Thus, through the synergistic effect of the dispersant and the grinding media in step S201, sufficient wetting and initial dispersion of the ceramic powder are ensured.
[0035] Step S202: The nanoparticles are added to a pre-dissolved binder and dispersed using a homogenizer to obtain a second treated body. This process produces a second treated body with excellent adhesion and rheological properties. For example, the binder can be polyvinyl butyral (PVB) resin.
[0036] Step S203: The first processing body and the second processing body are mixed by high-energy ball milling to obtain a uniformly dispersed microcrystalline glass ceramic slurry. This ensures that the slurry is highly uniform at both the macroscopic and microscopic levels, further eliminates agglomerates, and guarantees the performance consistency of the final product.
[0037] Step S204: Cast the microcrystalline glass ceramic slurry to form a second green ceramic tape.
[0038] In some embodiments, the mass of the nanoparticles is 0.1% to 10% of the mass of the microcrystalline glass-ceramic powder. This can increase the sintering shrinkage rate of the second green ceramic belt, making it better match the shrinkage rate of the ferrite material (first green ceramic belt), thereby ensuring the integrity of the multilayer transformer structure and preventing cracking. Exemplarily, the mass of the nanoparticles is 0.1%, 0.5%, 1%, 3%, 5%, 8%, or 10% of the mass of the microcrystalline glass-ceramic powder.
[0039] In some embodiments, the nanoparticles include one or more of alumina, zirconium oxide, silicon carbide, titanium carbide, and aluminum nitride.
[0040] In some embodiments, the conductive paste is silver paste; for step S30, the method of forming through holes on the first and second green ceramic tapes and filling the through holes with conductive paste includes: Step S301: A laser is used to drill holes in the first and second green ceramic tapes to form through holes with a diameter of 50 μm to 300 μm. Laser drilling technology allows for the high-precision fabrication of micropores on the green ceramic tapes to meet the requirements of high-density integration. For example, the through hole diameter can be 50 μm, 75 μm, 100 μm, 150 μm, 200 μm, 250 μm, or 300 μm.
[0041] Step S302: Fill the through-holes with silver paste containing a solid content greater than or equal to 85%. This ensures that the sintered through-holes have extremely high conductivity and minimal resistance. At the same time, the high solid content effectively suppresses sintering shrinkage voids, ensuring the reliability of the electrical connection. For example, the solid content can be 85%, 87%, 90%, or 95%.
[0042] Step S303: The silver paste in the through-holes is dried at a set temperature, ranging from 50°C to 120°C. This achieves rapid solidification and morphological stability of the silver paste, preventing paste flow and protecting the mechanical structure of the green ceramic tape. For example, the set temperature can be 50°C, 60°C, 80°C, 100°C, 110°C, or 120°C. Thus, through steps S301 to S303, after the silver paste in the through-holes of the first and second green ceramic tapes is dried, the through-holes become conductive through-holes 103. The first green ceramic tape with conductive through-holes 103 is the first through-hole-filling green ceramic tape 101, and the second green ceramic tape with conductive through-holes 103 is the second through-hole-filling green ceramic tape 102. The primary coil layer 104 and secondary coil layer 105 on the first through-hole-filling green ceramic tape 101 are electrically connected to their respective conductive through-holes 103. It should be noted that, in step S60, multiple first green ceramic tapes are stacked to form a cover layer. When it is necessary to electrically connect the stacked transformer to devices such as circuit boards, the cover layer used as the lower cover can also be laser-drilled to form conductive vias 103, so as to facilitate electrical connection with the conductive vias 103 in the intermediate electrode layer.
[0043] In some embodiments, the method for step S40, printing a primary coil layer 104 and a secondary coil layer 105 on the first through-hole green ceramic tape 101, includes: Step S401: Using silver paste with a solid content greater than or equal to 85%, a primary coil layer 104 and a secondary coil layer 105 are printed on the upper surface of the first through-hole green ceramic tape 101. The distance between the primary coil layer 104 and the secondary coil layer 105 can be greater than 100 μm. The spacing between the coils can be designed as needed, and this application does not limit it.
[0044] Step S402: Dry the first through-hole green ceramic tape 101 printed with primary coil layer 104 and secondary coil layer 105 at a preset temperature; the preset temperature is 50°C to 120°C, for example, the preset temperature can be 50°C, 60°C, 80°C, 100°C, 110°C or 120°C.
[0045] In some embodiments, for step S70, the method of stacking two capping layers and an intermediate electrode layer together to form a bar block includes: Step S701: Stack the two capping layers and the intermediate electrode layer in a predetermined order to form a laminate.
[0046] Step S702: Perform isostatic pressing on the stacked layers to form a block. The isostatic pressing temperature is 50℃-90℃, the pressure is 20MPa-100MPa, and the processing time is 10 minutes-30 minutes. For example, the isostatic pressing temperature can be 50℃, 60℃, 70℃, 80℃, or 90℃; the isostatic pressing pressure can be 20 MPa, 40 MPa, 60 MPa, 80 MPa, or 100 MPa; and the processing time can be 10 minutes, 15 minutes, 20 minutes, 25 minutes, or 30 minutes.
[0047] In some embodiments, during the cooling stage after sintering the laminated monomers, the cooling rate is from 0.1 °C / min to 2 °C / min. This slow cooling effectively solves the problems of interfacial stress concentration and structural cracking caused by the difference in thermal expansion coefficients of heterogeneous materials during sintering. For example, the cooling rate can be 0.1 °C / min, 0.5 °C / min, 1.0 °C / min, 1.5 °C / min, or 2 °C / min.
[0048] This application also provides a multilayer transformer, which is manufactured using the multilayer transformer manufacturing method provided in any of the above embodiments; the multilayer transformer has the same technical effects as the multilayer transformer manufacturing method provided in the foregoing embodiments, and will not be described again here.
[0049] The following description is based on specific embodiments.
[0050] Example 1 The specific implementation steps of the multilayer transformer fabrication method are as follows: Step S10: The first green ceramic tape is made from ferrite powder with a magnetic permeability of μ=420 using a casting process. The length and width of the first green ceramic tape are 200mm and 180mm, respectively.
[0051] Step S201: Mix the microcrystalline glass ceramic powder with a dispersant, a solvent and a grinding medium, and perform preliminary dispersion for 12 hours to obtain a first processed body, wherein the microcrystalline glass ceramic powder is a BaO-ZnO-MgO-SiO2 system.
[0052] Step S202: Add the nanoparticles to the pre-dissolved binder and disperse them in a homogenizer for 2 hours to obtain a second processed body. After vacuum standing to remove bubbles for 1 hour, the second processed body is formed. The mass of the nanoparticles is 0.5% of the mass of the microcrystalline glass ceramic powder.
[0053] Step S203: Mix the first processing body and the second processing body by high-energy ball milling for 12 hours to obtain a uniformly dispersed microcrystalline glass ceramic slurry.
[0054] Step S204: Cast the microcrystalline glass ceramic slurry to form a second green ceramic tape.
[0055] Step S301: Use a laser to drill holes in the first and second green ceramic tapes to form through holes with a diameter of 200 μm.
[0056] Step S302: Fill the through holes with silver paste with a solid content of 85%.
[0057] Step S303: Dry the silver paste in the through hole at a set temperature of 70°C.
[0058] Step S401: A primary coil layer 104 and a secondary coil layer 105 are printed on the upper surface of the first through-hole green ceramic tape 101 using silver paste with a solid content of 88%, wherein the spacing between the coils is 110 μm.
[0059] Step S402: Dry the first hole-filling green ceramic tape 101, which is printed with primary coil layer 104 and secondary coil layer 105, at a preset temperature of 70°C.
[0060] Step S50: Stack multiple coil-filled green ceramic tapes and multiple second-filled green ceramic tapes 102 in a preset order to form an intermediate electrode layer.
[0061] Step S60: Stack multiple first green ceramic tapes to form a cover layer, wherein the thickness of the cover layer is 0.5 mm.
[0062] Step S701: Stack the two capping layers and the intermediate electrode layer in a predetermined order to form a laminate.
[0063] Step S702: Perform isostatic pressing on the stacked layers to form a block, wherein the isostatic pressing temperature is 70℃, the pressure is 40MPa, and the processing time is 20 minutes.
[0064] Step S80: Cut the block to form multiple stacked monomers.
[0065] Step S90: Sinter the laminated monomers to obtain a laminated transformer, wherein the cooling rate during the cooling stage is 0.2℃ / min.
[0066] Table 1:
[0067] Table 1 compares the performance of the multilayer transformer prepared in this application with that of a pure ferrite transformer. Based on the performance comparison data shown in Table 1, it can be concluded that the multilayer transformer with air-gap material prepared in this application has significant advantages in both electromagnetic and thermal performance compared to the pure ferrite transformer. Specifically, under the same input voltage, the air-gap transformer achieves a higher output voltage (1247V vs. 1003V), indicating higher energy conversion efficiency or a better turns ratio design. Simultaneously, its primary inductance (65.2μH vs. 35.98μH) and secondary inductance (2.77mH vs. 1.56mH) are significantly improved, demonstrating stronger energy storage capacity and magnetic coupling efficiency. Most importantly, after ten minutes of operation, the surface temperature of the air-gap transformer is significantly lower (37℃ vs. 51℃), indicating a substantial reduction in power consumption and heat loss, resulting in higher stability and reliability.
[0068] In summary, the LTCC-based multilayer transformer and its fabrication method provided in this application, formed using LTCC technology, effectively solves the key technical problem of interface cracking during the co-firing of heterogeneous materials by optimizing the magnetic circuit design and introducing a buffer structure. Specifically, the microcrystalline glass ceramic acts as a magnetoresistive confinement element in the magnetic circuit, enabling precise control of the magnetoresistive path, thereby reducing interlayer leakage inductance by more than 30% and significantly improving the primary-secondary coupling coefficient. The uniform distribution of nanoparticles within the microcrystalline glass ceramic, through anchoring and regional nano-stress release structures, coordinates the stress between the ferrite and the microcrystalline glass ceramic during co-firing, resulting in an interface crack rate of less than 5% and a yield rate exceeding 95%. Furthermore, this design significantly improves high-frequency energy conversion efficiency, reduces device heat generation by approximately 20%, and enables dielectric withstand voltages exceeding 3kV, fully meeting the requirements of high-frequency, high-power applications.
[0069] It should be understood that, in the embodiments of this application, unless otherwise expressly specified and limited, the terms "connection," "fixed connection," "contact," etc., should be interpreted broadly. Those skilled in the art can understand the specific meanings of the various terms in the embodiments of this application according to the specific circumstances.
[0070] For example, the "connection" can be a fixed connection, a rotating connection, a flexible connection, a sliding connection, a one-piece molding, an electrical connection, a contact connection, or other connection methods; it can be a direct connection, or an indirect connection through an intermediate medium, or a connection within two components or an interaction between two components.
[0071] For example, a "fixed connection" can be a component that can be directly or indirectly fixedly connected to another component; a fixed connection can include mechanical connection, welding, bonding or integral molding, etc., wherein mechanical connection can include riveting, bolting, threaded connection, keying, snap-fit connection, locking connection, plugging, etc., and bonding can include adhesive bonding and solvent bonding, etc.
[0072] It should also be understood that the “parallel” or “perpendicular” described in the embodiments of this application can be understood as “approximately parallel” or “approximately perpendicular”.
[0073] It should also be understood that the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Features specified as "first" or "second" may explicitly or implicitly include one or more of that feature.
[0074] In the embodiments of this application, unless otherwise expressly specified and limited, "above" or "below" the second feature can mean that the first feature and the second feature are in direct contact, or that the first feature and the second feature are in indirect contact through an intermediate medium. Furthermore, "above," "on top of," and "over" the second feature can mean that the first feature is directly above or diagonally above the second feature, or simply that the first feature is at a higher horizontal level than the second feature. "Below," "below," and "under" the second feature can mean that the first feature is directly below or diagonally below the second feature, or simply that the first feature is at a lower horizontal level than the second feature.
[0075] It should also be understood that the terms “length,” “width,” “up,” “down,” “front,” “back,” “left,” “right,” “vertical,” “horizontal,” “top,” “bottom,” “inner,” and “outer,” etc., indicate the orientation or positional relationship (if any) based on the orientation or positional relationship shown in the accompanying drawings. They are used only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on this application.
[0076] The above description is merely a specific embodiment of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of protection of the claims. In conclusion, the above description is merely a preferred embodiment of the technical solution of this application and is not intended to limit the scope of protection of this application. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the scope of protection of this application.
Claims
1. A method for manufacturing a multilayer transformer, characterized in that, include: The first green ceramic belt was made from ferrite powder using a casting process. The second green ceramic tape is made from microcrystalline glass-ceramic powder using a casting process; Through holes are formed on the first green ceramic tape and the second green ceramic tape, and conductive paste is filled into the through holes to obtain the first hole-filled green ceramic tape and the second hole-filled green ceramic tape, respectively. A primary coil layer and a secondary coil layer are printed on the first hole-filling green ceramic tape to form a coil hole-filling green ceramic tape; Multiple coil-filling green ceramic tapes and multiple second-filling green ceramic tapes are stacked in a predetermined order to form an intermediate electrode layer; Multiple sheets of the first green ceramic tape are stacked together to form a cover layer; The two capping layers and the intermediate electrode layer are stacked together to form a bar block, wherein the intermediate electrode layer is located between the two capping layers; The block is cut to form multiple stacked monomers; The laminated monomers are sintered to obtain a laminated transformer.
2. The method for manufacturing a multilayer transformer as described in claim 1, characterized in that, The process of forming a second green ceramic tape from microcrystalline glass-ceramic powder using a casting process includes: Microcrystalline glass-ceramic powder is mixed with dispersant, solvent and grinding media, and then initially dispersed to obtain a first processed body; The nanoparticles were added to a pre-dissolved binder and dispersed using a homogenizer to obtain a second treated body. The first processing body and the second processing body are mixed by high-energy ball milling to obtain a uniformly dispersed microcrystalline glass ceramic slurry; The microcrystalline glass-ceramic slurry is cast to form the second green ceramic tape.
3. The method for manufacturing a multilayer transformer as described in claim 2, characterized in that, The nanoparticles include one or more of the following: alumina, zirconium oxide, silicon carbide, titanium carbide, and aluminum nitride.
4. The method for manufacturing a multilayer transformer as described in claim 2, characterized in that, The mass of the nanopowder is 0.1% to 10% of the mass of the microcrystalline glass-ceramic powder.
5. The method for manufacturing a multilayer transformer as described in any one of claims 1-4, characterized in that, The magnetic permeability of the ferrite powder is greater than 400.
6. The method for manufacturing a multilayer transformer as described in any one of claims 1-4, characterized in that, The microcrystalline glass-ceramic powder includes one or more of the following systems: MgO-Al2O3-SiO2, SiO2-Al2O3-ZnO-MgO, BaO-ZnO-MgO-SiO2, and BaO-Al2O3-SiO2.
7. The method for manufacturing a multilayer transformer as described in any one of claims 1-4, characterized in that, The step of stacking the two capping layers and the intermediate electrode layer together to form a bar block includes: The two cap layers and the intermediate electrode layer are stacked in a predetermined order to form a laminate; The stacked layers are subjected to isostatic pressing to form a block, wherein the isostatic pressing temperature is 50℃-90℃, the pressure is 20MPa-100MPa, and the processing time is 10 minutes-30 minutes.
8. The method for manufacturing a multilayer transformer as described in any one of claims 1-4, characterized in that, During the cooling stage after sintering the laminated monomers, the cooling rate is from 0.1℃ / min to 2℃ / min.
9. The method for manufacturing a multilayer transformer as described in any one of claims 1-4, characterized in that, The conductive paste is silver paste; The step of forming through holes on the first and second green ceramic tapes and filling the through holes with conductive paste includes: A laser is used to drill holes in the first and second green ceramic tapes to form through holes with a diameter of 50 μm to 300 μm; The through holes are filled with silver paste with a solid content greater than or equal to 85%; The silver paste in the through-hole is dried at a set temperature, which is between 50°C and 120°C.
10. A multilayer transformer, characterized in that, The multilayer transformer is manufactured using the multilayer transformer manufacturing method as described in any one of claims 1-9.